2012
DOI: 10.1002/dta.1338
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of new psychoactive substances: A retrospective study in hair

Abstract: New psychoactive substances are conquering the drug scene. Police seize different colourful packages with exceptional names. They are declared as 'bath salts', 'plant food', or 'research chemical powders'. Little is known about the actual prevalence of these drugs. Reanalysis of hair samples from routine cases concerning the presence of new psychoactive substances or 'smart drugs' should provide insight into changing patterns of designer drugs. All hair samples from 2009 and 2010 that originally tested positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 25 publications
3
84
0
Order By: Relevance
“…However, mephedrone was often the sole product component. This finding together with others reports [31,32] that suggested higher prevalence of mephedrone over the other synthetic stimulants indicated that mephedrone might be produced and distributed in a different way from the other synthetic stimulants. This hypothesis is supported by our data, which showed that the increase in mephedrone use occurred in the year before the increase in use of methylone, MDPV, BZP and TFMPP.…”
Section: Discussionsupporting
confidence: 78%
“…However, mephedrone was often the sole product component. This finding together with others reports [31,32] that suggested higher prevalence of mephedrone over the other synthetic stimulants indicated that mephedrone might be produced and distributed in a different way from the other synthetic stimulants. This hypothesis is supported by our data, which showed that the increase in mephedrone use occurred in the year before the increase in use of methylone, MDPV, BZP and TFMPP.…”
Section: Discussionsupporting
confidence: 78%
“…Para-(4)-phenyl-substituted amphetamines, which have emerged in recent years, with novel psychoactive substances and forensic cases (Helander et al, 2014;Johansen and Hansen, 2012;Rohrich et al, 2012;Rust et al, 2012). Users report that the subjective effects of 4-methlylmethcathinone (Carhart-Harris et al, 2011) and 4-fluoroamphetamine (Erowid, 2014) are comparable to those of MDMA.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, whereas the determination of synthetic cannabinoids in urine and blood will therefore be faced with the issue of identifying several metabolites often not well known, hair analysis can be focussed directly on the parent drug. Nevertheless, to date, only few studies deal with the determination of NPS in hair [19][20][21][22][23][24]. Two studies reported in the recent literature for the determination of synthetic cannabinoids used extraction methods based on incubation in concentrated sodium hydroxide solutions, providing the dissolution of the keratin matrix [19,20].…”
Section: Introductionmentioning
confidence: 98%